KAJI EKSPERIMENTAL KINERJA TURBIN ULIR ARCHIMEDES BERDASARKAN SUDUT KEMIRINGAN POROS TURBIN - Jayanto, Septian Dwi; Hatib, Rustan; Muchsin, Muchsin (Foristek, 2025)
This study aims to evaluate the effect of variations in the shaft inclination angle, namely 22°, 24°, 26°, 28°, and 30° on the performance of the Archimedes screw turbine with the experimental method carried out using a half-scale turbine model with a constant discharge of 0.0014 m³/s and an increase in torque (1-4 Nm). The parameters analyzed include rotational speed (RPM), output power, and efficiency at each torque level (1–4 Nm). The results show that the maximum efficiency of 61.81% is achieved at an angle of 22° with a torque of 3 Nm. Although the 30° angle produces higher output power, its efficiency is lower due to the larger head value (0.58 m compared to 0.435 m at 22°), which increases input power but is not offset by a comparable increase in output. In addition, at steeper angles, there is an increase in leakage and overflow due to less-than-optimal screw filling. This study concludes that the combination of 22° angle and 3 Nm torque is the most efficient configuration for a small-scale screw turbine system. This study can serve as a reference for designing a micro-hydro power generation system based on a screw turbine.